Accounting for free digital services and household production: An application to Facebook (Meta) - Paul Schreyer (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2022)
Choice experiments show that individuals attribute significant value to digitally-enabled services such as social media. We integrate this consumer value into an accounting framework by treating it as the value of own-account production by households of a particular type of leisure services. Time spent by households, along with social media and information technology capital services constitute the relevant inputs. We derive a quality-adjusted unit cost index for such household-produced leisure services whereby the number of network users acts as the main vehicle to capture quality change. These quality adjustment effects turn out to be key when assessing the quantitative importance of own-account leisure services. To illustrate, we consider an extended measure of activity (EMA) that encompasses gross domestic product (GDP) and own-account household production of digitally-enabled leisure services. A simulation for the United States shows that the effects due to Facebook use alone would cause the EMA to grow anywhere between about +0.04 and about +0.2 percentage points per year more than United States real growth GDP between 2004 and 2017, depending on the size of network effects.
Keywords: C43; D60; E01; E23; O3; O4; 330; national accounts; welfare measurement; GDP mismeasurement; productivity slowdown; free digital services; GDP-B